2017
DOI: 10.1159/000453668
|View full text |Cite
|
Sign up to set email alerts
|

Impaction and Prediction: Does Ureteral Wall Thickness Affect the Success of Medical Expulsive Therapy in Pediatric Ureteral Stones?

Abstract: Objective: The study aimed to evaluate the predictive value of ureteral wall thickness (UWT) and stone-related parameters for medical expulsive therapy (MET) success with an alpha blocker in pediatric upper ureteral stones. Patients and Methods: A total of 35 children receiving MET ureteral stones (<10 mm) were evaluated. Patients were divided into 2 subgroups where MET was successful in 18 children (51.4%) and unsuccessful in 17 children (48.6%). Prior to management, stone size, stone density (in Hounsfield u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 43 publications
1
6
0
Order By: Relevance
“…Studies have revealed well that the thickness of the ureteric wall surrounding the stone could be a reliable sign of such alterations which seem to increase parallel to the severity of impaction [12]. Related with this issue, the possible predictive value of the ureteral wall thickness (UWT) has been well evaluated to assess the degree of stone impaction and in one of our studies, we were able to demonstrate a signifcant relationship between the UWT values and obstruction degree in patients with acute ureteral obstruction [12,13,14]. In addition, we were able to show the predictive value of UWT assessment on the outcomes of medical and interventional procedures for such stones [12,15,16].…”
Section: Introductionsupporting
confidence: 56%
“…Studies have revealed well that the thickness of the ureteric wall surrounding the stone could be a reliable sign of such alterations which seem to increase parallel to the severity of impaction [12]. Related with this issue, the possible predictive value of the ureteral wall thickness (UWT) has been well evaluated to assess the degree of stone impaction and in one of our studies, we were able to demonstrate a signifcant relationship between the UWT values and obstruction degree in patients with acute ureteral obstruction [12,13,14]. In addition, we were able to show the predictive value of UWT assessment on the outcomes of medical and interventional procedures for such stones [12,15,16].…”
Section: Introductionsupporting
confidence: 56%
“…Studies have revealed that the thickness of the ureteric wall surrounding the stone could be a reliable sign of such alterations which tend to increase parallel to the severity of tissue changes [19]. The possible predictive value of the UWT was evaluated to assess the degree of stone impaction and we were able to demonstrate a signifcant relationship between the UWT values and the degree obstruction in cases with upper tract stones [20,21]. More importantly, the predictive value of UWT assessment on the outcomes of medical and interventional procedures have also been demonstred in our previous studies [19,22,23].…”
Section: Introductionmentioning
confidence: 77%
“…A certain percentage of such ureteral strictures can be highly morbid and recurrent which could require possible several endoscopic and/or other procedures (including reconstructive approaches) [4,7,8]. Postoperative ureteral strictures is reported to occur in 1-4% of patients after ordinary URS; however, it occurs in 7.8-24% of patients when URS is performed for impacted stones [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, Tuerxun et al [40] emphasized the role of the ureteral wall thickness, due to inflammatory reaction-induced tissue changes derived from stone impact into the ureteral wall, as a predictive factor for final stone expulsion rates. The use of bromelain can prevent and treat this edematous reaction, which is an additional obstacle to the descent of the stone [41].…”
Section: Discussionmentioning
confidence: 99%